PENGARUH DEWAN DIREKSI, RISK MANAGEMENT COMMITTEE DAN KONSENTRASI KEPEMILIKAN TERHADAP ENTERPRISE RISK MANAGEMENT - Hanifah Khairunnisa Masri; Muhamad Muslih (ITB AAS INDONESIA Surakarta, 2022)
This study aims to examine the effect of the board of directors, ownership concentration and risk management committee on the disclosure of enterprise risk management in manufacturing sector family companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample selection technique used was purposive sampling and obtained 30 manufacturing sector families for the 2016-2020 period so that the total sample used in this study was 150 samples. The data analysis method used is panel data regression analysis using Eviews version 11. Based on the results of the study, the variables of the board of directors, concentration of ownership and risk management committee simultaneously have a significant effect on enterprise risk management disclosure. Partially, the board of directors’ variable has a significant positive effect and ownership concentration has a significant negative effect on enterprise risk management disclosure. Meanwhile, the risk management committee has no effect on the disclosure of enterprise risk management. Keywords : Board of Directors, Concentration of Ownership, Enterprise Risk Management Management Committee.